Neurodevelopmental outcomes of infants born to mothers with SARS-CoV-2 infections during pregnancy: a national prospective study in Kuwait - Mariam Ayed; Alia Embaireeg; Mais Kartam; Kiran More; Mafaza Alqallaf; Abdullah AlNafisi; Zainab Alsaffar; Zainab Bahzad; Yasmeen Buhamad; Haneen Alsayegh; Wadha Al-Fouzan; Hessa Alkandari (BMC Pediatrics, 2022)
Abstract Background An increasing proportion of women are infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during pregnancy. Intrauterine viral infections induce an increase in the levels of proinflammatory cytokines, which inhibit the proliferation of neuronal precursor cells and stimulate oligodendrocyte cell death, leading to abnormal neurodevelopment. Whether a maternal cytokine storm can affect neonatal brain development is unclear. The objective of the present study was to assess neurodevelopmental outcomes in neonates born to mothers with SARS-CoV-2 infections during pregnancy. Methods In this prospective cohort study, the neurodevelopmental status of infants (N = 298) born to women with SARS-CoV-2 infections during pregnancy was assessed at 10–12 months post-discharge using the Ages and Stages Questionnaire, 3rd edition (ASQ-3). The ASQ-3 scores were classified into developmental delays (cutoff scores ≤ 2 standard deviations (SDs) below the population mean) and no delays (scores > 2 SDs above the population mean). Results The majority (90%) of the infants born to mothers with SARS-CoV-2 infections during pregnancy had favorable outcomes and only 10% showed developmental delays. Two of the 298 infants tested positive for SARS-CoV-2, and both had normal ASQ-3 scores. The majority of the pregnant women had SARS-CoV-2 infections during their third trimester. The risk of developmental delays among infants was higher in those whose mothers had SARS-CoV-2 infections during the first (P = 0.039) and second trimesters (P = 0.001) than in those whose mothers had SARS-CoV-2 infections during the third trimester. Conclusion The neurodevelopmental outcomes of infants born to mothers with SARS-CoV-2 infections seem favorable. However, more studies with larger sample sizes and longer follow-up periods are required.